ANALISIS IMPLEMENTASI KEBIJAKAN KETERWAKILAN PEREMPUAN DALAM DAFTAR CALON LEGISLATIF OLEH PARTAI POLITIK DI KPU PROVINSI GORONTALO - Wilvon Malahika; Lisda Van Gobel; Sofyan Alhadar (JIEM : Journal Of International Entrepreneurship And Management, 2026)
The policy requiring a minimum of 30 percent women's representation in legislative candidate lists is an important affirmative action measure to promote gender equality in political representation. However, its implementation at the regional level continues to face administrative challenges that may lead to electoral disputes. This study examines the implementation of this policy and the factors influencing of Gorontalo Province. A qualitative case study approach was employed, with data collected through in-depth interviews with eleven informants, observations, and document analysis, and analyzed using an interactive data analysis model. The findings indicate that, although women's representation exceeded the mandatory 30 percent threshold overall, one electoral district experienced a decline in women's representation, resulting in an electoral dispute and a repeat election. This situation was influenced by the commitment of policy implementers, regulatory compliance, resource capacity, and inconsistent administrative procedures. The study concludes that compliance with the administrative quota alone does not necessarily ensure substantive women's political representation at the local level.